Helicon waves in the magnetotail - Lakhina, G.S.; Sharma, A.S.; Papadopoulos, K. (My University, 2009)
The helicon modes are studied in Earth's magnetotail using the Harris sheet as a model of its equilibrium. The plasma sheet is divided into two regions: In region 1 both the electrons and the ions are treated as magnetized, whereas in region 2 the electrons are treated as magnetized but the ions are unmagnetized. The eigenmode equation for the low-frequency, parallel propagating right-hand polarized modes is solved for the two cases, namely, (1) the uniform regions and (2) the inhomogeneous case. The eigenvalues and the eigenfunctions are obtained for the symmetric and antisymmmetric helicon modes. The case of uniform regions predicts lower frequencies for both the symmetric and antisymmetric modes than that of the inhomogeneous case. For typical plasma sheet parameters, the wave frequencies are found to be in the range of ∼(1–50) mHz for the symmetric modes, and ∼(5–100) mHz for the antisymmetric helicon modes. The wavelengths (along x direction) associated with the helicon modes are in the range of ∼(0.3–9) RE. The antisymmetric mode does not allow flux crossing across the neutral sheet axis. The symmetric helicon mode does allow flux crossing leading to the change in the magnetic topology, and thus, it must involve reconnection.
Keywords: Magnetotail; Helicon waves; Helicon modes; Inhomogeneous